Moving Online? How to Effectively Deliver Virtual Fitness. (March 2021) - Culos-Reed, Nicole; Wurz, Amanda; Dowd, Justine; Capozzi, Lauren
Abstract : Supplemental digital content is available in the text. Apply It!: By reading this article, health and fitness professionals will gain knowledge, skills, and confidence to effectively deliver virtual fitness, incorporate evidence-informed behavior change strategies into virtual fitness, and optimize safety and client success online.